Risk Diversification by European Financial Conglomerates - Jan Frederik Slijkerman; Dirk Schoenmaker; Casper de Vries (Tinbergen Institute, 2005)
We study the dependence between the downside risk of European banks and insurers. Since the downside risk of banks and insurers differs, an interesting question from a supervisory point of view is the risk reduction that derives from diversification within large banks and financial conglomerates. We discuss the limited value of the normal distribution based correlation concept, and propose an alternative measure which better captures the downside dependence given the fat tail property of the risk distribution. This measure is estimated and indicates better diversification benefits for conglomerates versus large banks.
Keywords: G21; G22; G28; C49; 330; Financial conglomerates; Banking; Insurance; Diversification; Extreme Value Theory